Influence of abutment and connection type on implant-abutment connection rigidity: an in vitro study - Teresa Almeida Mendes; Luís Miguel Vilhena; Jaime Portugal; João Caramês; Amílcar Lopes Ramalho; Luís Pires Lopes (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2022)
Objectives: To evaluate the effects of the abutment material and the connection type on the implant-abutment connection rigidity. Methods: The study evaluated eighteen implants with three different types of connections: external-hexagon, tri-channel, and conical connection. Half of the implants were connected to titanium abutments, and the other half to zirconia abutments, forming six study groups (n=3). The implants were submitted to 1,200,000 load cycles with a force amplitude of 90 N. During load application, the implant-abutment connection rigidity was determined in each cycle. The values obtained were analyzed with the two-way ANOVA test according to the abutment and connection types. Results: Rigidity tended to increase during loading cycles. The abutment material did not influence rigidity (p=0.883). The external-hexagon connection presented lower rigidity than the internal connections, with statistically significant differences (p=0.013). Conclusions: The abutment material does not influence the implant-abutment connection's rigidity. The external-hexagon connection proved to be less rigid and stable than the internal connections.